Industrial catalysis and separations : innovations for process intensification - Reddy, B. M; Raghavan, K. V (Apple Academic Press, 2014)
With contributions from experts from both the industry and academia, this book presents the latest developments in the identified areas. In addition, a thorough and updated coverage of the traditional aspects of heterogeneous catalysis such as preparation, characterization and use in well-established technologies such as nitration, ammoxidation and hydrofluorination is included. This book incorporates appropriate case studies, explanatory notes, and schematics for more clarity and better understanding.